Cold Chain Maintenance and Vaccine Stock Management Practices at Public Health Centers Providing Child Immunization Services in Jimma Zone, Oromia Regional State, Ethiopia: Multi-Centered, Mixed Method Approach (Dove Medical Press, 2021)
Diriba Feyisa Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Diriba Feyisa Tel +251916892180Email diriba.feyisa@yahoo.comBackground: Cold chain maintenance is the spine of an immunization program.Objective: To examine the status of cold chain maintenance and evaluate knowledge of cold chain handlers and practices of vaccine management at public health centers providing immunization services in Jimma zone.Methods: An institutional-based cross-sectional study supplemented with a qualitative method was conducted in 41 randomly selected health centers providing immunization service in districts of Jimma zone from October 31 to November 30, 2019. Pre-tested self-administered questionnaires and observation checklists developed from an effective vaccine management assessment tool (EVMAT) were used to collect quantitative data. Key informants were selected using the purposive sampling technique and an in-depth interview was conducted. Quantifiable data were analyzed using SPSS version 20 and chi-square was used to test the presence of association (p-value < 0.05). Qualitative data were analyzed by thematic analysis and triangulated with quantitative findings.Results: All public health centers had at least functional ice-lined refrigerators while 28 (68.3%) public health centers had functional deep freezers. Of the cold chain handlers, 120 (82.9%) had fair knowledge. Vaccine storage was appropriate per the World Health Organization's vaccine storage code in ice-lined refrigerators in 11 (24.4%) public health centers. Cold chain handlers' years of service, types of training, availability of funds for cold chain maintenance, and availability of cold chain equipment at public health centers showed the presence of significant association with vaccine cold chain management practice.Conclusion: The majority of cold chain handlers showed inadequate knowledge while a significant number showed poor practice of preserving the vaccines' cold chain. Cold chain maintenance was not adequate in public health centers, necessitating attentive efforts of providing proper management of vaccine cold chains at immunization delivery points.Keywords: cold chain management, maintenance, vaccine, public health centers, Jimma, southwest Ethiopia